DEVELOPING ENGLISH READING MATERIAL BASED ON PROBLEM BASED LEARNING FOR GRADE XII STUDENTS OF LIGHT VEHICLE TECHNIQUE AT SMK SWASTA DWIWARNA MEDAN - Desi Matondang; Masitowarni Siregar; Rafika Dewi Nasution (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2019)
This study aims to develop English reading materials needed by students of Vocational School and develop English reading materials for students of Light Vehicle Technique based on Problem Based Learning. The research was conducted by Research and Development (R and D) design through six phases; gathering information and data, analyzing data, designing new materials, validating by experts, revising and final product. It was conducted in SMK Swasta Dwiwarna Medan, especially grade XII. The data were gathered by administering interview and distributing questionnaire results prove that the students need English reading materials which contain English lecturer and the second from English teacher. It means that the developing reading materials categorized as suitable or appropriate for grade XII of Light Vehicle Technique.Key Words: Research and development (R and D), reading materials, Light Vehicle Technique